Pretreatment with xylanase and its significance in hemicellulose removal from mixed hardwood kraft pulp as a process step for viscose. (10th July 2016) - Kaur, Prabhjot; Bhardwaj, Nishi K.; Sharma, Jitender
Highlights: Xylanase aided hemicellulose removal and its significance. HPLC profiling of xylanases and their reaction products. Effect of different enzyme doses prior to alkali extraction on pulp properties. XRD and SEM analysis of xylanase treated and alkali extracted pulps. Finding the appropriate xylanase dose prior to alkali extraction. Abstract: The upturn of viscose fiber market has triggered an augmented dissolving pulp usage over the last decade. Dissolving pulp is feasible to obtain from kraft pulp after two essential steps including hemicellulose removal and subsequent pulp activation. Prerequisite of conversion being hemicellulose reduction can be gently done by using xylanase treatment prior to alkali extraction. Herein, the significance of xylanase treatment and the optimum xylanase dose required in conjunction with subsequent alkali extraction was investigated. An increase in xylanase dose prior to alkali extraction had no significant effect on pentosans while the Fock reactivity and viscosity both improved at the dose of 50 AXU/g. Also, alkali extraction without xylanase pretreatment resulted in decreased Fock reactivity, alpha cellulose, brightness and viscosity of paper grade pulp. A moderate dose of xylanase prior to alkali extraction can thus be used to facilitate the hemicellulose removal while simultaneously protecting the native structure of cellulose.